(untitled) (Jurnal Elektronika dan Telekomunikasi, 2022)
In the development of telecommunications in Indonesia, cellular networks, especially 4G, have grown rapidly since the launch of 4G LTE services. In the implementation of LTE, an antenna that has performance values of bandwidth, working frequency, VSWR, and gain that meets the specifications was needed. This research aims to study a microstrip antenna for LTE applications at a frequency of 2.3 GHz on its effect on the gain and bandwidth parameters using the 21 array method and the truncated corner which was simulated using HFSS software. The microstrip antenna was made using FR4 substrate with a thickness (h) of 1.6 mm and a dielectric constant of 4.4 with an expected working frequency of 2.3 GHz with the desired parameters return loss < -10 dB, VSWR < 1.5, gain > 2 dB, and bandwidth > 200 MHz in the simulation. Based on the simulation results of the microstrip antenna with the 21 truncated corner array method, the return loss value= 18.171 dB, VSWR= 1.281, gain= 3.963 dB, and bandwidth= 283 MHz, which worked at a frequency of 2.3 GHz. Meanwhile, based on the results of the antenna measurements that have been implemented, the return loss value was= 11.07 dB, and the VSWR= 1.49, which works at a frequency of 2.2 GHz.